Low-Voltage Activating, Fast Responding Electro-thermal Actuator Based on Carbon Nanotube Film/PDMS Composites - Aouraghe, Mohamed Amine; Mengjie, Zhou; Qiu, Yiping; Fujun, Xu (Advanced fiber materials (Online), 2021)
The electro-thermal actuators (ETA) are smart devices that can convert electric energy into mechanical energy under electro-heating stimulation, showing great potential in the fields of soft robotics, artificial muscle and aerospace component. In this study, to build a low-voltage activating, fast responding ETA, a robust and flexible carbon nanotube film (CNTF) with excellent electrical and thermal conductivity was adopted as the conductive material. Then, an asymmetric bilayer structured ETA was manufactured by coating a thin layer of polydimethylsiloxane (PDMS) with high coefficient of thermal expansion (9.3 × 10 –4 °C −1 ), low young’s modulus (2.07 MPa) on a thin CNTF (~ 11 μm). The as-produced CNTF/PDMS composite ETA exhibited a large deformation (bending angle ~ 324°) and high electro heating performance (351 °C) at a low driving voltage of 8 V within ~ 12 s. The actuated movement and the generated heat could be controlled by adjusting the driving voltages and showed almost the same values in 20 cycles. Furthermore, the influences of the PDMS thickness and driving voltage on CNTF/PDMS composite ETA performance were systematically investigated. The CNTF/PDMS soft robotic hand which can lift 5.1 times and crab 1.3 times of its weight demonstrated its potential capability.